stainless steel foil

CN123022829APending Publication Date: 2026-10-30NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023500.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-28
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0030]本公开的不锈钢箔减少损伤的形成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is a stainless steel foil that reduces the formation of damage. The stainless steel foil of the present disclosure has a foil body composed of stainless steel, in any face in the foil body, defines as coarse particles particles having a circle-equivalent diameter of 6.0 μm or more, among the coarse particles, defines as specific particles particles in which, among the element contents contained in the particles, the Al content, the Mg content, or the Ti content is the highest, and when the number density of the specific particles is 40.0 particles / cm 2 Hereinafter, the number ratio of the specific particles to the coarse particles is 80% or more. 0.3591≦4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)≦3.0943(1) where, in the element symbols of formula (1), the Al content, the Mg content, and the Ti content contained in the coarse particles are substituted with mass %.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to steel foil, and more specifically to stainless steel foil. Background Technology

[0002] Stainless steel, due to its excellent corrosion resistance and fatigue strength, is processed into various shapes for a wide range of applications. In recent years, the use of stainless steel foil, which is processed into foil shape, has become increasingly common. Furthermore, in this specification, the term "steel foil" refers to steel sheet with a thickness of 150 μm or less.

[0003] Stainless steel foil is used in various applications, such as as a substrate material for electronic devices, a current collector material for primary and secondary batteries, an external casing material for primary and secondary batteries, and a spring material for supporting the read / write heads of hard disk drives. Specifically, Japanese Patent Application Publication No. 2014-183254 (Patent Document 1), International Publication No. 2016 / 031192 (Patent Document 2), and International Publication No. 2020 / 004595 (Patent Document 3) disclose stainless steel foil for use in various applications.

[0004] Patent Document 1 discloses a ferritic stainless steel foil for solar cell substrates, containing 14-18% Cr by mass, with a Vickers hardness of Hv250 or higher. Even after undergoing a film-forming heat treatment at a temperature range of 450-600°C for at least one minute, the Vickers hardness remains above Hv250. Patent Document 1 also discloses that when this stainless steel foil is used to manufacture solar cell units using a roll-to-roll method, it can suppress wrinkles caused by substrate bending during continuous processes following the high-temperature process (film-forming heat treatment), exhibiting good board continuity.

[0005] Patent Document 2 discloses a ferritic stainless steel foil used as a catalyst carrier in exhaust gas purification devices. It contains, by mass percent, less than 0.020% C, less than 2.0% Si, less than 1.0% Mn, less than 0.010% S, less than 0.050% P, 10.0–25.0% Cr, 0.05–0.50% Ni, 0.14–0.25% Ti, 0.001–0.10% Al, 0.02–0.10% V, and less than 0.020%, with the remainder consisting of Fe and impurities. Its Vickers hardness is greater than 200 and less than 350. Patent Document 2 discloses that this stainless steel foil exhibits excellent corrugated forming processability, resistance to shape changes at high temperatures, and manufacturability.

[0006] The stainless steel foil disclosed in Patent Document 3 is a stainless steel foil current collector for the positive electrode of a secondary battery. It contains, by mass%, C: 0.001-0.030%, Si: 0.01-1.00%, Mn: 0.01-1.00%, Cr: 12-18%, and contains at least one of Sn and Ti. Either Sn or Ti satisfies the greater of (a) Sn: 0.01-1.00%, (b) Ti: 0.10%, or 16 (%C + %N). The remaining portion consists of Fe and impurities. The impurities are limited to stainless steel with P: 0.050% or less, S: 0.030% or less, and N: 0.0300% or less. The thickness is 1-20 μm, and the surface hardness is Hv300 or less according to Vickers hardness tester. Patent document 3 discloses that the stainless steel foil not only has mechanical strength, but also increases the contact area with the positive electrode active material or positive electrode agent to ensure conductivity, and also ensures corrosion resistance to alkali or electrolyte.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2014-183254

[0010] Patent Document 2: International Publication No. 2016 / 031192

[0011] Patent Document 3: International Publication No. 2020 / 004595 Summary of the Invention

[0012] The technical problem that the invention aims to solve

[0013] However, stainless steel foil sometimes requires corrosion resistance under harsh conditions. For example, in the case of its application to the solar cell substrate proposed in Patent Document 1, resistance to corrosion from the installation environment is required. Furthermore, in the case of its application to the exhaust purification device proposed in Patent Document 2, resistance to corrosive gases contained in the exhaust is required. And, further, in the case of its application to the current collector proposed in Patent Document 3, resistance to electrolytes and the like is also required.

[0014] On the other hand, the stainless steel foil described above is very thin, with a thickness of less than 150 μm. Therefore, during the manufacturing process, minute defects or unevenness are easily formed on the surface. Hereinafter, this specification refers to minute defects or unevenness formed on or inside the steel foil as "damage." Furthermore, this specification distinguishes damage from pinholes (through holes in the foil thickness direction) formed in the stainless steel foil. In the case of damage, there are more lattice defects represented by dislocations or point defects; therefore, depending on the formation process of pinholes, damage may sometimes form around the pinholes. Moreover, as mentioned above, damage contains more lattice defects; therefore, when damage forms in the stainless steel foil, it may become the starting point of corrosion. Furthermore, among damages, especially large damages, are more likely to become the starting point of corrosion. Here, this specification refers to large pits formed on the surface of the steel foil as "depressions." Therefore, in stainless steel foils requiring excellent corrosion resistance under harsh conditions, it is preferable to reduce damage, especially the formation of depressions.

[0015] As described above, patent documents 1 to 3 disclose stainless steel foils for various applications. However, patent documents 1 to 3 do not address damage formed on the surface of the stainless steel foil.

[0016] The purpose of this disclosure is to provide a stainless steel foil that reduces damage formation.

[0017] Methods for solving technical problems

[0018] The stainless steel foil disclosed herein,

[0019] It has a foil body made of stainless steel.

[0020] In any facet of the foil body,

[0021] Particles with an equivalent circumference diameter of 6.0 μm or more are defined as coarse particles.

[0022] Among the coarse particles

[0023] Among the elements contained in the particles, Al, Mg, or Ti have the highest content.

[0024] When particles whose Al content, Mg content, and Ti content satisfy equation (1) are defined as specific particles,

[0025] The number density of the specific particles is 40.0 particles / cm³. 2 the following,

[0026] The specific particles constitute more than 80% of the total number of coarse particles.

[0027] 0.3591≦4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)≦3.0943(1)

[0028] Here, in the element symbols of equation (1), the Al, Mg, and Ti contents contained in the coarse particles are substituted by mass % in the element symbols. If the coarse particles do not contain the corresponding elements, "0" is substituted into the element symbols.

[0029] Invention Effects

[0030] The stainless steel foil disclosed herein reduces the formation of damage. Detailed Implementation

[0031] The inventors of this invention have conducted detailed research on reducing the formation of damage in stainless steel foil. Firstly, stainless steel foil sometimes contains coarse particles, which are different from the parent phase (stainless steel phase), and are represented by inorganic particles called inclusions, such as metallic precipitates, crystals, metals, and compounds of metalloids with oxygen, nitrogen, carbon, and sulfur. On the other hand, when the foil body also contains coarse particles with different hardness or ductility, represented by inclusions, damage may form in the stainless steel foil. The inventors of this invention have conducted detailed research and determined that, in particular, certain coarse particles with an equivalent circumference diameter of 6.0 μm or more at the particle interface are prone to causing damage to the parent material. Hereinafter, particles with an equivalent circumference diameter of 6.0 μm or more will be referred to as "coarse particles" in this specification.

[0032] Next, the inventors of this invention focused on the composition of coarse particles and conducted a detailed study on coarse particles that are prone to causing damage. The results showed that among coarse particles, the Al, Mg, or Ti content was the highest, and particles with Al, Mg, and Ti contents that satisfy Equation (1) had a significant impact on the damage to stainless steel foil.

[0033] 0.3591≦4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)≦3.0943(1)

[0034] Here, in the element symbols of equation (1), the Al, Mg, and Ti contents contained in the coarse particles are substituted by mass % in the element symbols. If the coarse particles do not contain the corresponding elements, "0" is substituted into the element symbols.

[0035] Define Fn1 = 4.5579Al / (Al + Mg + Ti) - 4.5579Mg / (Al + Mg + Ti) + 1.7321Ti / (Al + Mg + Ti). Furthermore, define F... Al =Al / (Al+Mg+Ti). F Al This represents the ratio of Al content to the sum of Al, Mg, and Ti content in the coarse particles. Similarly, F is defined as... Mg =Mg / (Al+Mg+Ti). F Mg This represents the ratio of Mg content to the sum of Al, Mg, and Ti content in the coarse particles. Similarly, F is defined as... Ti =Ti / (Al+Mg+Ti). F Ti This represents the ratio of Ti content to the sum of Al, Mg, and Ti content in the coarse particles. That is, it is equivalent to Fn1 = 4.5579F Al -4.5579F Mg +1.7321F Ti .

[0036] As defined above, Fn1 is an index for determining the type of coarse particles. In this context, coarse particles (particles with an equivalent circumference diameter of 6.0 μm or more) in stainless steel foil are inclusions or metallic precipitates and crystals. Specifically, the stainless steel foil may contain particles with an equivalent circumference diameter of 6.0 μm or more, such as inclusions like SiO2, CaO, MgO, Al2O3, TiN, MgAl2O4, and their composite particles. The inventors of this invention have discovered through detailed research that inorganic particles, especially TiN and MgAl2O4, exhibit very high hardness and low ductility compared to other inclusions or precipitates. Therefore, during the manufacturing process of stainless steel foil, the presence of coarse TiN and MgAl2O4 in the steel foil can easily lead to damage in the manufactured stainless steel foil.

[0037] In the stainless steel foil of this embodiment, the coarse particles with an Fn1 content of 0.3591 to 3.0943 are almost entirely TiN, MgAl2O4, or composite particles thereof. Therefore, in this specification, coarse particles with an Fn1 content of 0.3591 to 3.0943 are defined as "specific particles". That is, when the foil body contains a large number of specific particles, a large amount of damage is easily formed during the manufacturing process of the stainless steel foil. Therefore, reducing the number density of specific particles contained in the foil body may reduce the damage to the stainless steel foil.

[0038] Therefore, the inventors of this invention investigated reducing the number density of specific particles contained in the foil body to reduce damage to the stainless steel foil. The inventors' research clarified that if the number density of specific particles is 40.0 particles / cm³... 2 Hereinafter, damage formation can be suppressed if other configurations of this embodiment are satisfied.

[0039] On the other hand, within the foil body, there exists a situation where even when the number density of specific particles is reduced to 40.0 particles / cm², [the problem persists]. 2 The following situations also fail to suppress the formation of damage. Therefore, the inventors of this invention have addressed the issue of having a specific particle number density of 40.0 particles / cm³. 2 The following stainless steel foil, as the main body of the foil, was further investigated using various methods to reduce damage. The results showed that increasing the proportion of specific particles within the coarse particles further reduced damage to the stainless steel foil.

[0040] Therefore, in the stainless steel foil of this embodiment, the number density of specific particles in the foil body is set to 40.0 particles / cm². 2 Furthermore, the ratio of specific particles to coarse particles is set to 80% or more. As a result, the stainless steel foil of this embodiment reduces the formation of damage.

[0041] In the stainless steel foil substrate, the number density of specific particles is set to 40.0 particles / cm². 2 The following examples demonstrate how the proportion of specific particles relative to coarse particles is further set to 80% or more to reduce the formation of damage to stainless steel foil.

[0042] The purpose of the stainless steel foil in this embodiment, based on the above insights, is as follows.

[0043] [1] A stainless steel foil,

[0044] It has a foil body made of stainless steel.

[0045] In any facet of the foil body,

[0046] Particles with an equivalent circumference diameter of 6.0 μm or more are defined as coarse particles.

[0047] Among the coarse particles

[0048] Among the elements contained in the particles, Al, Mg, or Ti have the highest content.

[0049] When particles whose Al content, Mg content, and Ti content satisfy equation (1) are defined as specific particles,

[0050] The number density of the specific particles is 40.0 particles / cm³. 2 the following,

[0051] The specific particles constitute more than 80% of the total number of coarse particles.

[0052] 0.3591≦4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)≦3.0943(1)

[0053] Here, in the element symbols of equation (1), the Al, Mg, and Ti contents contained in the coarse particles are substituted by mass % in the element symbols. If the coarse particles do not contain the corresponding elements, "0" is substituted into the element symbols.

[0054] [2] Stainless steel foil as described in [1],

[0055] In the foil body,

[0056] Among the specific particles

[0057] When defining a specific spinel particle as one whose Ti content satisfies equation (2) among the elemental contents of the particles,

[0058] The number density of the specific spinel grains is 4.5 grains / cm³. 2 the following.

[0059] Ti / (Al+Mg+Ti)≦0.05(2)

[0060] Here, in the element symbols of equation (2), the Al, Mg, and Ti contents contained in the coarse particles are substituted by mass%. When the coarse particles do not contain the corresponding element, "0" is substituted into the element symbol.

[0061] [3] Stainless steel foil as described in [1],

[0062] The chemical composition of the foil body, in mass % is

[0063] Contains Ti: 0.10–1.00%.

[0064] [4] Stainless steel foil as described in [2],

[0065] The chemical composition of the foil body, in mass % is

[0066] Contains Ti: 0.10–1.00%.

[0067] [5] Stainless steel foil as described in any one of [1] to [4],

[0068] The foil body is made of ferritic stainless steel or austenitic stainless steel.

[0069] The stainless steel foil of this embodiment will now be described. In the following description, the stainless steel foil will be simply referred to as "steel foil".

[0070] [Stainless steel foil]

[0071] In this specification, "steel foil" refers to a steel plate with a thickness of 150 μm or less. That is, the stainless steel foil of this embodiment has a thickness of 150 μm or less. Furthermore, the stainless steel foil of this embodiment comprises a foil body made of stainless steel. The stainless steel foil may also have a composition other than the foil body. For example, a resin coating may be formed on the surface of the foil body, or a coating primarily composed of an inorganic compound may be formed.

[0072] [Foil body]

[0073] As described above, in this embodiment, the foil body is made of stainless steel. That is, in this embodiment, the type of stainless steel constituting the foil body is not particularly limited. The stainless steel can be, for example, ferritic stainless steel, martensitic stainless steel, austenitic stainless steel, ferritic-martensitic dual-phase stainless steel, or ferritic-austenitic dual-phase stainless steel.

[0074] Preferably, the stainless steel used in this embodiment is a ferritic stainless steel or an austenitic stainless steel. When the stainless steel is an austenitic stainless steel, the steel grade can be, for example, SUS301, SUS301L, SUS301J1, SUS302B, SUS304, SUS304Cu, SUS304L, SUS304N1, SUS304N2, SUS304LN, SUS304J1, SUS304J2, SUS305, SUS309S, SUS310S, SUS312L, SUS315J1, SUS305, SUS309S, SUS310S, SUS312L, SUS315J1, SUS304N2, SUS304NN, SUS304J1, SUS304N2 ... Any one of 15J2, SUS316, SUS316L, SUS316N, SUS316LN, SUS316Ti, SUS316J1, SUS316J1L, SUS317, SUS317L, SUS317LN, SUS317J1, SUS317J2, SUS836L, SUS890L, SUS321, SUS347, SUSXM7, and SUSXM15J1.

[0075] Furthermore, the chemical composition of austenitic stainless steel can also be, by mass%, C: less than 0.150%, Si: less than 1.00%, Mn: less than 2.00%, P: less than 0.045%, S: less than 0.0300%, Cr: 16.00–20.00%, Ni: 6.00–15.00%, Al: less than 0.010%, N: less than 0.100%, Mo: 0–2.50%, Ti: 0– 0.500%, Nb: 0~0.12%, V: 0~1.00%, Zr: 0~0.100%, Ta: 0~0.50%, Hf: 0~0.10%, Co: 0~0.50%, B: 0~0.0100%, Ca: 0~0.0200%, Mg: 0~0.0200%, rare earth elements: 0~0.0100%, Cu: 0~3.00%, and the remainder being chemical components composed of Fe and impurities.

[0076] When the stainless steel is ferritic, the type of steel is not particularly limited, and any well-known ferritic stainless steel can be used. The type of ferritic stainless steel can also be any of the following as specified in JIS G 4305 (2015): SUS405, SUS410L, SUS429, SUS430, SUS430LX, SUS430J1L, SUS434, SUS436L, SUS436J1L, SUS443J1, SUS444, SUS445J1, SUS445J2, SUS447J1, and SUSXM27. Ferritic stainless steel grades can also be any of the following as specified in ASTM A240 (2006): 403, 405, 409L, 410, 410L, 410S, 415, 420J1, 420J2, 420, 429, 429J1, 430, 430J1L, 430LX, 430Ti, 434, 436, 436J1L, 439, 441, 444, 445, 445J1, 445J2, 446, 447, and 448.

[0077] In this case, the chemical composition of ferritic stainless steel can also be expressed as a percentage by mass: C: ≤0.150%, Si: ≤1.00%, Mn: ≤1.00%, P: ≤0.050%, S: ≤0.030%, Cr: 12.00–20.00%, Ni: 0.01–0.50%, Mo: 0.01–2.50%, Al: ≤0.010%, N: ≤0.100%, Ti: 0~1.00%, Nb: 0~0.80%, V: 0~1.00%, Zr: 0~0.80%, Ta: 0~0.50%, Hf: 0~0.10%, Co: 0~0.50%, B: 0~0.0100%, Ca: 0~0.0200%, Mg: 0~0.0200%, rare earth elements: 0~0.0100%, Cu: 0~3.00%, and the remainder being chemical components composed of Fe and impurities.

[0078] More preferably, the chemical composition of the foil body in this embodiment contains 0.10 to 1.00% Ti by mass. In this case, the corrosion resistance of the stainless steel foil is further improved. On the other hand, when the chemical composition of the foil body contains 0.10 to 1.00% Ti by mass, the amount of coarse TiN contained in the foil body increases. As a result, the number density of specific particles increases, which may easily lead to damage to the stainless steel foil. However, in the stainless steel foil of this embodiment, even if the chemical composition of the foil body contains 0.10 to 1.00% Ti by mass, the number density of specific particles is set to 40.0 particles / cm³. 2 The following method sets the ratio of specific particles to coarse particles to be more than 80%, thereby reducing the formation of damage to stainless steel foil.

[0079] The thickness of the foil body in this embodiment is not particularly limited, but is, for example, 3 to 80 μm. If the foil body is too thin, it is difficult to manufacture foil bodies of uniform thickness. On the other hand, if the foil body is too thick, sometimes the desired characteristics corresponding to the application are not obtained. Preferably, the thickness of the foil body is 5 to 60 μm.

[0080] [Specific particles]

[0081] In this embodiment, among the coarse particles (particles with an equivalent circumference diameter of 6.0 μm or more) in the stainless steel foil body, the Al, Mg, or Ti content is the highest among the elemental contents of the particles. When particles whose Al, Mg, and Ti contents satisfy equation (1) are defined as specific particles, the number density of specific particles is 40.0 particles / cm³. 2 The following refers to a specific particle size distribution that accounts for more than 80% of the total number of coarse particles.

[0082] 0.3591≦4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)≦3.0943(1)

[0083] Here, in the element symbols of equation (1), the Al, Mg, and Ti contents contained in the coarse particles are substituted by mass % . When the coarse particles do not contain the corresponding element, the element symbol is substituted with "0".

[0084] Fn1 (=4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)) is an indicator for determining the type of coarse particles. As mentioned above, F... Al (=Al / (Al+Mg+Ti)), F Mg (=Mg / (Al+Mg+Ti)), F Ti When (=Ti / (Al+Mg+Ti)), it can be recorded as Fn1=4.5579F Al -4.5579F Mg +1.7321F Ti .

[0085] In this specification, coarse particles with an Fn1 value of 0.3591 to 3.0943 are defined as "specific particles". As mentioned above, in the foil body of stainless steel foil, so-called specific particles with an Fn1 value of 0.3591 to 3.0943 are almost all TiN, MgAl2O4, or composite particles thereof. Furthermore, among coarse particles, TiN, MgAl2O4, and their composite particles have very high hardness and low ductility compared to other coarse particles. Therefore, compared to other coarse particles, damage is more likely to occur at the interface of specific particles. Therefore, in this embodiment, the number density of specific particles is reduced.

[0086] Specifically, in the stainless steel foil of this embodiment, the number density of specific particles in the foil body is reduced to 40.0 particles / cm². 2 As a result, damage formation can be suppressed if other configurations of this embodiment are satisfied. The preferred upper limit for the specific particle number density is 39.5 particles / cm³. 2 The preferred density is 35.0 cells / cm. 2 30.0 pieces / cm is preferred. 2 Further optimization to 25.0 cells / cm 2 Further optimization to 20.0 pieces / cm 2Furthermore, in this embodiment, the number density of a specific particle is preferably low. That is, the lower limit of the number density of a specific particle is not particularly limited, and can also be 0.1 particles / cm³. 2 The lower limit for the number density of a specific particle can be 1.0 particles / cm³. 2 It can also be 3.0 pieces / cm 2 It can also be 5.0 pieces / cm 2 .

[0087] The stainless steel foil of this embodiment further specifies the ratio of specific particles to coarse particles. As described above, the coarse particles in the foil body of the stainless steel foil may include, for example, SiO2, CaO, MgO, Al2O3, TiN, MgAl2O4, and composite particles thereof. Among these, the specific particles (TiN, MgAl2O4, and composite particles thereof) have particularly high hardness. In other words, it is considered that coarse particles other than the specific particles are softer than the specific particles and have less impact on damage formation.

[0088] On the other hand, coarse particles other than the specific particles can also be the starting point of damage. Furthermore, excessively reducing the number density of specific particles can also lead to damage to the stainless steel foil during the manufacturing process. Therefore, in the stainless steel foil of this embodiment, coarse particles other than the specific particles are minimized as much as possible. As a result, the ratio of specific particles to coarse particles increases. In other words, by increasing the ratio of specific particles to coarse particles and reducing coarse particles other than the specific particles, damage formation in the stainless steel foil is reduced.

[0089] Specifically, in the stainless steel foil of this embodiment, the number density of specific particles in the foil body is reduced to 40.0 particles / cm². 2 Based on the following, the ratio of specific particles to coarse particles is further set to 80% or more. As a result, the stainless steel foil of this embodiment can suppress the formation of damage. The preferred lower limit of the ratio of specific particles to coarse particles is 81%, and more preferably 82%. The upper limit of the ratio of specific particles to coarse particles is not particularly limited and can also be 100%.

[0090] Furthermore, in the stainless steel foil of this embodiment, the number density of specific particles in the foil body is 40.0 particles / cm². 2 The following applies: the ratio of specific particles to coarse particles must be 80% or higher; the number density of coarse particles is not specifically limited. The actual number density of coarse particles is approximately 50.0 particles / cm³. 2 The lower limit for the number density of coarse particles is not particularly limited and can also be 0.1 particles / cm³. 2 .

[0091] In this embodiment, the number density of specific particles and the ratio of specific particles to coarse particles are obtained by the following method. First, a test piece is made from the stainless steel foil of this embodiment, with the surface or cross-section (polished surface) of the foil body as the observation surface. SEM-based observation and EDS-based elemental analysis (EDS analysis) are performed on the observation surface of the manufactured test piece. First, particles are detected from the image contrast. Specifically, for any observation area set within the observation surface, the SEM stage is controlled to scan and detect particles exposed on the surface. Furthermore, the particle detection method can employ an automated particle detection system or a commercially available MQA (Metal Quality Analyzer). More specifically, as an MQA, for example, the AZtec manufactured by Oxford Corporation can be used. The determination and analysis methods are described below.

[0092] Particle detection using scanning electron microscopy (SEM) is performed based on the contrast of the reflected electron image. In this embodiment, particles with an equivalent circle diameter of 6.0 μm or more are defined as "coarse particles." Therefore, the size of one pixel in the resolved reflected electron image is at least 0.7 μm. 2 The following methods are used to set the magnification, etc. Furthermore, to ensure measurement resolution, a field emission scanning electron microscope (FE-SEM) is preferred. Specifically, a JSM-IT500HR manufactured by Nippon Electronics Corporation can be used as the FE-SEM. Typical conditions for meeting the above measurement requirements when using this FE-SEM are: detector: BED-C reflective electron detector, magnification: 80x, accelerating voltage: 20.0kV, working distance (WD): 10.0mm, and illumination current: 80%.

[0093] For the particles detected above, elemental concentration analysis (EDS analysis) was performed. In the EDS analysis, the resolution was 2048, the residence time (collection time per pixel) was 3 μs, the input signal was a backscattered electron image (BSE), the number of frames (number of scans in the same field of view) was 1, and the lower limit for the detected particle size was 6 pixels. The EDS could be manufactured by Oxford Instruments Co., Ltd.: ULTIM MAX 65.

[0094] Furthermore, the equivalent circle diameter of each particle can be obtained through image analysis. Additionally, the elements to be detected in the EDS analysis are set as Cr, Fe, Ni, Mo, C, N, O, Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl. That is, for particles determined based on contrast, the contents of Cr, Fe, Ni, Mo, C, N, O, Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl are determined by EDS analysis.

[0095] In this embodiment, the stainless steel foil may contain contaminants or other contaminants that could lead to erroneous particle detection. Therefore, in this embodiment, during EDS analysis, if any element other than Cr, Fe, Ni, Mo, C, N, and O is detected, specifically Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl, it is identified as a "particle". In other words, in this embodiment, a "coarse particle" is defined as a particle with an equivalent circle diameter of 6.0 μm or more determined by contrast, and where any element other than Cr, Fe, Ni, Mo, C, N, and O is detected, specifically Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl, specifically a particle, is detected at a mass percentage of 1 or more.

[0096] If the total number of coarse particles as defined above exceeds 100, change the field of view and repeat the measurement. Furthermore, calculate Fn1 based on the Al, Mg, and Ti contents obtained from the above EDS analysis. Fn1 is obtained by rounding the obtained value to its fifth decimal place.

[0097] As defined above, among the coarse particles and the elements detected above, those with the highest Al, Mg, or Ti content among elements other than Cr, Fe, Ni, Mo, C, N, and O (i.e., Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl), and satisfying an Fn1 value of 0.3591–3.0943, are defined as "specific particles". The field of view is changed, and the measurement is repeated, counting coarse particles and specific particles separately until more than 100 coarse particles are found. Based on the number of specific particles obtained and the total area of ​​the field of view used for EDS analysis, the number density of specific particles (particles / cm²) is calculated. 2 In addition, the number density of specific particles (particles / cm³) 2The percentage (%) is obtained by rounding the second decimal place of the obtained value. Based on the number of specific particles and the number of coarse particles, the percentage (%) of the specific particles relative to the coarse particles is calculated. Furthermore, the percentage (%) of the specific particles relative to the coarse particles is obtained by rounding the first decimal place of the obtained value.

[0098] [Specific spinel grains]

[0099] In this embodiment, the stainless steel foil further includes specific particles within the foil body. When defining particles with Ti content satisfying formula (2) as specific spinel particles, the preferred number density of these specific spinel particles is 4.5 particles / cm³. 2 the following.

[0100] Ti / (Al+Mg+Ti)≦0.05 (2)

[0101] Here, the element symbols in equation (2) are substituted with the mass percentage of the Al, Mg, and Ti content contained in the coarse particles. If the coarse particles do not contain the corresponding element, "0" is substituted into the element symbol.

[0102] Define Fn2 = Ti / (Al + Mg + Ti). As described above, in the foil body of the stainless steel foil in this embodiment, the so-called specific particles are almost entirely TiN, MgAl2O4, or composite particles of them. The so-called specific spinel particles are specific particles that have a low Ti content. That is, the so-called specific spinel particles are almost entirely MgAl2O4. In other words, Fn2 is an indicator representing the proportion of specific spinel particles in the specific particles.

[0103] The inventors of this invention have discovered that specific spinel particles, particularly MgAl2O4 particles, are prone to becoming the starting point for damage in stainless steel foil. These specific spinel particles may also become the starting point for the formation of composite particles with TiN. Therefore, in the stainless steel foil of this embodiment, it is preferable to reduce the number of specific spinel particles in the foil body to 4.5 per cm. 2 The following is an example: The number density of specific particles in the foil body is 40.0 particles / cm². 2 The following sets the ratio of specific particles to coarse particles at 80% or more, and the specific spinel particles at 4.5 per cm. 2 The following steps can further reduce damage formation in stainless steel foil.

[0104] A more preferred upper limit for the number density of specific spinel grains is 4.4 grains / cm³. 2 A more optimal ratio of 4.3 cells / cm is preferred. 2The lower limit for the number density of specific spinel grains is not particularly limited and can also be 0.0 grains / cm³. 2 The lower limit for the number density of a specific particle can be 0.1 particles / cm³. 2 It can also be 0.5 per cm. 2 It can also be 1.0 pieces / cm 2 .

[0105] In this embodiment, the number density of specific spinel particles is obtained by the following method. In the method described above for obtaining the number density of specific particles, Fn2 (=Ti / (Al+Mg+Ti)) is calculated from the obtained Al content, Mg content, and Ti content. Particles that are not only specific particles but also have an Fn2 of 0.05 or less are defined as "specific spinel particles". The number density of specific spinel particles (particles / cm²) is obtained based on the number of specific spinel particles obtained and the total area of ​​the field of view used for EDS analysis. 2 In addition, the number density of specific spinel grains (numbers / cm³) 2 Round the second decimal place of the obtained value.

[0106] [Applications of Stainless Steel Foil]

[0107] The application of the stainless steel foil in this embodiment is not particularly limited. On the other hand, as described above, the stainless steel foil of this embodiment can reduce the formation of damage, thereby suppressing corrosion that originates from damage and obtaining excellent corrosion resistance. Therefore, the application of the stainless steel foil of this embodiment is preferred among thin film materials requiring corrosion resistance. Specifically, the stainless steel foil of this embodiment can be used in a wide range of fields, such as substrate materials for electronic devices, current collector materials in primary and secondary batteries, external casing materials in primary and secondary batteries, and spring materials for supporting the heads of hard disk drives. It can also be used as a current collector material for solid-state batteries, which is envisioned for use in harsh environments.

[0108] [Manufacturing Method]

[0109] This section describes an example of a method for manufacturing the stainless steel foil according to this embodiment. Furthermore, the stainless steel foil of this embodiment can also be manufactured using methods other than the one described below. The manufacturing method described below is a preferred example of the method for manufacturing the stainless steel foil of this embodiment. The method for manufacturing the stainless steel foil of this embodiment includes a material preparation step, an intermediate cold rolling step, an annealing step, and a foil rolling step.

[0110] [Material Preparation Process]

[0111] In the material preparation process, a material having the same chemical composition as the main body of the foil is prepared as the substrate for the stainless steel foil. Here, "material" refers to an intermediate product used to manufacture the main body of the foil in this embodiment, and means a steel plate with a thickness of several hundred μm to several mm. The material is, for example, a hot-rolled coil. The material can also be a cold-rolled coil. The material can be prepared through manufacturing or by purchasing it from a third party. That is, the process of preparing the material is not particularly limited.

[0112] In the case of preparing raw materials, steel can be manufactured, for example, by the following methods: Molten steel with the desired chemical composition is produced. The molten steel is then used to produce castings (slabs, rough-rolled billets, or billets) via continuous casting. Alternatively, molten steel can be used to produce ingots (steel billets) via casting. If necessary, slabs, rough-rolled billets, or steel billets can also be rolled to produce steel billets.

[0113] The manufactured castings or ingots (slabs, unrolled billets, steel billets, or steel ingots) are hot-worked to produce steel plates (materials) with a thickness of several hundred μm to several mm. The hot-working method is not particularly limited; any known method may be used. Preferably, the hot-worked material is subjected to appropriate surface treatments such as pickling. At this time, impurities are removed from the surface of the material. The material of this embodiment is prepared according to the above steps.

[0114] [Intermediate cold rolling process]

[0115] In the intermediate cold rolling process, the prepared material is cold rolled to produce intermediate steel parts. Here, intermediate steel parts refer to intermediate products used to manufacture the foil body of this embodiment, and are steel plates with a thickness of tens to hundreds of μm. In the intermediate cold rolling process, cold rolling and annealing are repeated. At this time, cold rolling can be carried out, for example, using a continuous rolling mill or a reversible rolling mill equipped with multiple cold rolling mill stands.

[0116] Preferably, the total rolling yield in the intermediate cold rolling process is set to 95.0% or higher. The total rolling yield is defined as the ratio (%) of the thickness of the intermediate steel piece after the intermediate cold rolling process to the thickness of the raw material before the intermediate cold rolling process. When the total rolling yield is 95.0% or higher, the specific particles are separated, reducing their number density. On the other hand, if the total rolling yield is too low, the number density of specific particles in the manufactured stainless steel foil is too high, sometimes making it impossible to reduce damage formation. Therefore, in the intermediate cold rolling process of this embodiment, it is preferable to set the total rolling yield to 95.0% or higher.

[0117] Preferably, in the intermediate cold rolling process, the number of passes is set to 8 or more. The number of passes in cold rolling refers to the number of times the material passes through the cold rolling mill. Specifically, when cold rolling is performed with 8 passes, the material passes through the cold rolling mill and is cold rolled 8 times. When the number of passes is 8 or more, specific particles are segmented, which can reduce the number density of specific particles. On the other hand, if the number of passes is too few, the number density of specific particles in the manufactured stainless steel foil becomes too high, and sometimes it is not possible to reduce the formation of damage. Therefore, in the intermediate cold rolling process of this embodiment, it is preferable to set the number of passes to 8 or more.

[0118] More preferably, the number of passes is set to 10 or more. In this case, dividing the specific spinel particles reduces the number density of those particles. Therefore, in the intermediate cold rolling process of this embodiment, it is even more preferable to set the number of passes to 10 or more.

[0119] Preferably, in the intermediate cold rolling process, the rolling rate of each pass is set to 30% or more. The rolling rate of each pass in cold rolling refers to the average rolling rate of each pass. Furthermore, the rolling rate of each pass refers to the ratio (%) of the thickness of the material after that pass to the thickness of the material before that pass. A rolling rate of 30% or more in each pass allows for the segmentation of specific particles, reducing the particle density. On the other hand, if the rolling rate of each pass is too low, the particle density in the manufactured stainless steel foil becomes too high, sometimes failing to reduce damage formation. Therefore, in the intermediate cold rolling process of this embodiment, it is preferable to set the rolling rate of each pass to 30% or more. Based on the above process, the intermediate steel part of this embodiment is manufactured.

[0120] [Annealing process]

[0121] In the annealing process, the manufactured intermediate steel parts are subjected to annealing treatment. Bright annealing is preferred as the annealing treatment. Bright annealing is an annealing treatment performed in an extremely low oxygen atmosphere. Intermediate steel parts that have undergone bright annealing exhibit minimal surface oxidation and maintain their surface gloss. The extremely low oxygen atmosphere in bright annealing is preferably a mixture of H2 and N2 gases. The N2 fraction in the atmosphere is not particularly limited, but for example, it is 35% to 65% by volume.

[0122] Furthermore, the intermediate cold rolling process and the annealing process can be performed alternately multiple times. For example, the cold rolling and annealing processes can be repeated only with the number of passes referred to in the intermediate cold rolling process. For example, after performing the number of passes in the intermediate cold rolling process more than once, an annealing process can be performed once. That is, in this embodiment, since the number of passes in the intermediate cold rolling process is set to 8 or more, the annealing process can also be performed 8 or more times, or 7 or fewer times, or only once.

[0123] Here, in the intermediate cold rolling process, damage may occur at the interface between the base material and specific particles due to cold rolling. On the other hand, due to the repeated intermediate cold rolling and annealing processes, the damage is partially repaired by the annealing treatment. Therefore, in the intermediate cold rolling process, setting a higher rolling rate for each pass can reduce the number density of coarse particles, especially specific particles.

[0124] [Foil rolling process]

[0125] In the foil rolling process, the intermediate steel parts that have undergone annealing are cold rolled to manufacture the foil body of the desired thickness.

[0126] Preferably, the number of passes in the foil rolling process is set to four or more. As mentioned above, the number of passes in cold rolling refers to the number of times the material passes through the cold rolling mill. Specifically, when cold rolling is performed with four passes, the intermediate steel part is cold rolled four times by the cold rolling mill. If the number of passes is four or more, specific particles can be segmented, reducing the number density of specific particles. When the number of passes is four or more, coarse particles other than specific particles are further segmented, which can increase the ratio of specific particles to coarse particles. On the other hand, if the number of passes is too few, the number density of specific particles in the manufactured stainless steel foil becomes too high, and sometimes it is not possible to reduce the formation of damage. In this case, there is a situation where the ratio of specific particles to coarse particles cannot be sufficiently increased. Therefore, in the foil rolling process of this embodiment, it is preferable to set the number of passes to four or more.

[0127] Preferably, in the foil rolling process, the rolling rate of each pass is set to 20% to 30%. As described above, the rolling rate of each pass in cold rolling represents the average rolling rate of each pass. Furthermore, the rolling rate of each pass represents the ratio (%) of the thickness of the intermediate steel part after that pass to the thickness of the intermediate steel part before that pass. If the rolling rate of each pass is 20% or more, specific particles can be segmented, reducing the particle density. On the other hand, if the rolling rate of each pass is too high, damage may occur. Therefore, in the foil rolling process of this embodiment, it is preferable to set the rolling rate of each pass to 20% to 30%.

[0128] Based on the rolling conditions above, stainless steel foil can be manufactured in the following manner: in the soft inclusions other than the specific particles, the base material is extended and segmented with inhibitory damage, there are very few coarse particles larger than 6.0 μm, and the proportion of the specific particles to the coarse particles in this embodiment is more than 80%.

[0129] [Other processes]

[0130] The foil body of this embodiment is manufactured according to the above process. The stainless steel foil of this embodiment may also consist only of the foil body. In this case, the stainless steel foil of this embodiment can be manufactured through the manufacturing process described above. On the other hand, the stainless steel foil of this embodiment may also include components other than the foil body. As described above, for example, an insulating protective film such as a resin coating may be formed on the surface of the foil body. In this case, for example, after coating the surface of the manufactured foil body with a composition as a raw material for the resin coating, it can be cured by heat treatment to form a resin coating. For example, a resin coating may also be formed on the surface of the manufactured foil body by vapor deposition. That is, the foil body manufactured by the above-described foil rolling process can be subjected to known surface treatments to manufacture stainless steel foil.

[0131] The stainless steel foil of this embodiment is manufactured through the above manufacturing process. The stainless steel foil of this embodiment will be further described in detail below through examples. Furthermore, the examples described below are merely illustrative of the effectiveness of the stainless steel foil of this embodiment and do not limit the scope of the invention.

[0132] [Example 1]

[0133] Prepare the materials for each test number. It should be noted that the materials for each test number have a chemical composition equivalent to SUS430LX (steel grade “A” in Table 1), SUS444 (steel grade “B” in Table 1), or SUS304 (steel grade “C” in Table 1) as specified in JIS G4305 (2015).

[0134] [Table 1]

[0135]

[0136] For the materials of each test number, an intermediate cold rolling process was performed under the conditions described in Table 1 to manufacture intermediate steel parts for each test number. Furthermore, for the intermediate steel parts of each test number, a total of four bright annealing processes were performed between cold working and cold working. And, for the intermediate steel parts that underwent the fourth bright annealing, a foil rolling process was performed under the conditions shown in Table 1 to manufacture stainless steel foil for each test number.

[0137] [Evaluation Experiment]

[0138] The manufactured stainless steel foil was subjected to coarse particle observation tests and damage evaluation tests. Furthermore, in this embodiment, the stainless steel foil used in each evaluation test was not pre-ground.

[0139] [Observational test on coarse particles]

[0140] For each test number of stainless steel foil, an automated particle detection system (AZtec, Oxford Instruments) was used for the SEM and EDS analyses described above. Images of inorganic particles (inclusions) were acquired using a SEM (JSM-IT500HR, NJEOL Ltd.), and analysis of inorganic particles was performed using an EDS (ULTIMMAX65, Oxford Instruments Ltd.). The measurement conditions, SEM, and EDS settings used in the analysis are shown.

[0141] • Measurement area for one measurement: 20mm × 50mm

[0142] • Detector: BED-C reflective electron detector

[0143] • Observation magnification: 80x

[0144] • Accelerating voltage: 20.0kV

[0145] • Working distance (WD): 10.0mm

[0146] • Irradiation current: 80%

[0147] • Resolution: 2048

[0148] • Dwell time (collection time per pixel): 3μs

[0149] • Input signal: Biometric Image (BSE)

[0150] • Frame count (number of scans within the same field of view): 1

[0151] • Lower limit for detecting particle size: 6 pixels

[0152] Based on the above settings, the brightness and contrast of the SEM were appropriately adjusted to identify substances with an equivalent circle diameter (equivalent area equivalent circle diameter) of 2.22 μm or larger (substances different from the parent phase that may be inclusions) from the SEM image. EDS analysis was then performed on each identified substance.

[0153] The detection elements in EDS analysis are set as Cr, Fe, Ni, Mo, C, N, O, Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl. Based on the compositional analysis results of the analytes, analytes containing more than 1% by mass of Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl are defined as "particles". Based on the EDS analysis results, a database containing the size and composition values ​​of each particle within the measurement area is created. Using this database, coarse particles with an equivalent circumference diameter of 6.0 μm or greater are extracted. To suppress bias, the field of view is changed and this series of operations is repeated until the total number of coarse particles with an equivalent circumference diameter of 6.0 μm or greater exceeds 100, and then the database is used for analysis.

[0154] Among the coarse particles in the aforementioned database, those with the highest Al, Mg, or Ti content, and whose Fn1 ranges from 0.3591 to 3.0943, are defined as "specific particles." Here, the particle with the highest Al, Mg, or Ti content refers to the particle with the highest Al, Mg, or Ti content among Al, Mg, Ti, Si, Ca, V, Mn, Cu, Nb, P, S, Na, Cl, K, Zn, Br, Ag, Ba, Lu, W, and Tl. Furthermore, among specific particles, particles with an Fn2 value of 0.05 or less are defined as "specific spinel particles."

[0155] The number density of a specific particle was determined based on the number of specific particles and the total area of ​​the observation field used for EDS analysis. Furthermore, the ratio of the number of specific particles to the number of coarse particles was determined based on the number of coarse particles and the number of specific particles. Additionally, the number density of a specific spinel particle was determined based on the number of specific spinel particles and the total area of ​​the observation field used for EDS analysis. The number density of specific particles (particles / cm²) is shown in Table 2 for each test number. 2 ), the ratio of specific particles to coarse particles (%), and the number density of specific spinel particles (particles / cm³). 2 ).

[0156] [Table 2]

[0157]

[0158] [Damage Assessment Test]

[0159] The degree of damage was evaluated by observing the stainless steel foils for each test number using SEM. Specifically, visual tests were conducted to evaluate the surface of the stainless steel foils by visual inspection, and quantitative dent tests were performed to evaluate the degree of dents. In addition, the specimens used for observation were selected from test pieces that were closest to the specific particle number density values ​​shown for each test number in Table 2.

[0160] First, a visual inspection was conducted. Specifically, the magnification for SEM observation was set between 80x and 5000x, with different magnifications used in the overall and detailed evaluations. The presence or absence of damage was determined based on the contrast of dents or imperfections in the foil substrate, such as dislocations. As a result, if the number of defects was high and their severity significant, the evaluation was "NA (Not Acceptable)" in Table 2. If the number of defects was low and their severity minor, the evaluation was "G (Good)" in Table 2. If the number of defects was very small and their severity minimal, the evaluation was "E (Excellent)" in Table 2.

[0161] Next, a quantitative indentation test is performed. Here, an indentation is defined as a pit of particularly large size formed around a coarse particle. Therefore, in this embodiment, coarse particles are identified through the aforementioned coarse particle observation test, and the indentations formed around these coarse particles are quantitatively determined. More specifically, among the coarse particles identified by the coarse particle observation test, five coarse particles with large equivalent circle diameters are selected. Using a three-dimensional SEM, a surface profile is obtained centered on the identified coarse particles. The area of ​​the obtained surface profile is set to 47.6 μm x 63.5 μm, and the depth is set to an appropriate depth. Based on the obtained surface profile, the area (μm²) of the indentation is evaluated. 2 The area of ​​the depression (μm) and the depth of the depression were determined by SEM images and surface profiles. The lowest point of the surface profile was defined as the bottom of the depression. Furthermore, the area near the bottom of the depression, i.e., the location where the surface profile shows a maximum value, was defined as the outer periphery of the depression. For each test number, the same measurements were performed on five specific coarse particles to determine the area and depth of the depressions formed around each inclusion. Table 3 shows the maximum area (μm) of the depressions for each test number. 2 ), average area (μm) 2 ), maximum depth (μm), average depth (μm).

[0162] [Table 3]

[0163]

[0164] [Evaluation Results]

[0165] Referring to Tables 1 to 3, stainless steel foils numbered 1 to 7 were manufactured using the preferred manufacturing method described above. As a result, these stainless steel foils exhibited a specific particle number density of 40.0 particles / cm² within the stainless steel foil body. 2 The proportion of specific particles relative to coarse particles is above 80%. As a result, these stainless steel foils were visually assessed as having reduced damage formation. Furthermore, the maximum area of ​​the depression in these stainless steel foils is 600 μm. 2 Below, and the average area of ​​the depression is 400 μm. 2 The following reduces the depression that is a large-scale pit.

[0166] Furthermore, for the stainless steel foils tested (numbers 2-7), the intermediate cold rolling process involved more than 10 passes. As a result, the number density of specific spinel particles in these stainless steel foils was 4.5 particles / cm³. 2 As a result, these stainless steel foils were visually assessed as having further reduced damage formation. Furthermore, in these stainless steel foils, the maximum depth of the dent was less than 3.00 μm, and the depth of the dent was less than 2.00 μm, further reducing the extent of pitting.

[0167] On the other hand, for the stainless steel foil in test number 8, the rolling yield in each pass of the intermediate cold rolling process was too low. Furthermore, the number of passes in the foil rolling process was too few, resulting in an excessively low rolling yield in each pass. Consequently, the number density of specific particles in this stainless steel foil exceeded 40.0 particles / cm². 2 The proportion of specific particles relative to coarse particles is less than 80%. As a result, the stainless steel foil was visually assessed as not reducing damage formation. Furthermore, the maximum area of ​​the dent in the stainless steel foil is greater than 600 μm. 2 Furthermore, the average area of ​​the depression is higher than 400 μm. 2 It did not reduce the depression as a large-scale pit.

[0168] For the stainless steel foil in test number 9, the overall rolling yield in the intermediate cold rolling process was too low, and the rolling yield of each pass was also too low. As a result, the number density of specific particles in this stainless steel foil exceeded 40.0 particles / cm³. 2 As a result, the stainless steel foil was determined by visual inspection to have no effect on reducing damage formation. Furthermore, the maximum area of ​​the dent in the stainless steel foil exceeded 600 μm. 2 Furthermore, the average area of ​​the depression is higher than 400 μm. 2 It did not reduce the depression that was a large-scale pit.

[0169] The stainless steel foil in test number 10 had too few passes in the intermediate cold rolling process. Furthermore, the number of passes in the foil rolling process was also too low. As a result, the ratio of specific particles to coarse particles in this stainless steel foil was less than 80%. Consequently, this stainless steel foil was judged by visual inspection to have failed to reduce damage formation. Furthermore, the maximum area of ​​the dent in this stainless steel foil exceeded 600 μm. 2 Furthermore, the average area of ​​the depression is higher than 400 μm. 2 It did not reduce the depression that was a large-scale pit.

[0170] The stainless steel foil in test number 11 had too few passes in the intermediate cold rolling process. As a result, the number density of certain particles in this stainless steel foil exceeded 40.0 particles / cm³. 2 As a result, the stainless steel foil was determined by visual inspection to have failed to reduce damage formation. Furthermore, the maximum area of ​​the dents in the stainless steel foil exceeded 600 μm. 2 Furthermore, the average area of ​​the depression exceeds 400 μm. 2 It did not reduce the depression that was a large-scale pit.

[0171] In test 12, the stainless steel foil had too few passes in the foil rolling process. As a result, the number density of certain particles in this stainless steel foil exceeded 40.0 particles / cm³. 2 The proportion of specific particles relative to coarse particles was less than 80%. As a result, the stainless steel foil was visually assessed as not reducing damage formation. Furthermore, the maximum area of ​​the dents in the stainless steel foil exceeded 600 μm. 2 Furthermore, the average area of ​​the depression exceeds 400 μm. 2 It did not reduce the depression that was a large-scale pit.

[0172] The stainless steel foil in test number 13 had excessively low rolling yields in each pass of the intermediate cold rolling process. Furthermore, the number of passes in the foil rolling process was insufficient. As a result, the ratio of specific particles to coarse particles in this stainless steel foil was less than 80%. Consequently, visual inspection determined that this stainless steel foil did not reduce damage formation. Moreover, the maximum area of ​​the dents in this stainless steel foil exceeded 600 μm. 2 Furthermore, the average area of ​​the depression exceeds 400 μm. 2 It did not reduce the depression that was a large-scale pit.

[0173] [Example 2]

[0174] In Example 2, the relationship between the number density of specific particles, the ratio of specific particles to coarse particles, and the corrosion resistance of the stainless steel foil was investigated. Specifically, the corrosion resistance was investigated using stainless steel foils from tests 2, 4, 8, and 10 in Example 1. Table 4 shows the steel grade of the stainless steel foil for each test number, and the number density of specific particles (particles / cm³). 2 ), the ratio of specific particles to coarse particles (%), and the evaluation results of damage.

[0175] [Table 4]

[0176]

[0177] [Corrosion Resistance Evaluation Test]

[0178] This study envisions an application of this material in current collectors for all-solid-state secondary batteries, evaluating corrosion resistance using cyclic voltammetry (CV). First, 11 mm diameter test pieces are collected from the stainless steel foil substrate. One surface of the test piece is designated as the evaluation surface. On the evaluation surface of the test piece, the unfolded area ratio Sdr, as specified in ISO 25178-2:2012, is measured. The unfolded area ratio Sdr is an indicator of the rate of increase in surface area of ​​the test surface compared to a flat surface. Since the corrosion reaction originates at the surface of the stainless steel foil, a larger unfolded area ratio Sdr indicates a faster rate of corrosion development.

[0179] The unfolded area ratio (Sdr) of the evaluation surface of the test specimen was determined using a laser microscope. The laser microscope used was a Keyence VK-X100 manufactured by Keyence Corporation. The magnification was set to 2000x, and a measurement area of ​​280 μm × 200 μm was measured. Specifically, four locations within the measurement area were measured in a 145 μm × 109 μm field of view to obtain surface images, allowing measurement of the entire area. The four surface images were then concatenated using the accompanying image merger software to obtain a surface image of the 280 μm × 200 μm measurement area. From the surface shape curve obtained by resolving the surface image of the measurement area, a 0.3% region was cut off from the side with lower brightness to establish a reference plane, generating a three-dimensional image. At this point, a high-pass filter with a cutoff wavelength of 50 μm was used for filtering. A Gaussian filter was used for the filtering method. The unfolded area ratio (Sdr) as specified in ISO 25178-2:2012 was obtained from a 200 μm × 150 μm region of the obtained three-dimensional image.

[0180] Evaluation cells mimicking sulfide-based all-solid-state batteries were fabricated using test pieces with measured unfolded area ratios (Sdr) for each test number. Specifically, 0.12 g of a sulfide-based solid electrolyte was placed into a mold with an inner diameter of 11 mm, and pressure was applied at 300 MPa to form cylindrical particles of the sulfide-based solid electrolyte with a thickness of 700 μm and a bottom diameter of 11 mm. The sulfide-based solid electrolyte used was β-Li3PS4. The fabricated particles were placed on the evaluation surface of the test pieces for each test number. Furthermore, a cylindrical Li metal foil with a thickness of 1.2 mm and a bottom diameter of 11 mm was placed on the sulfide-based solid electrolyte particles. The sample was then placed in a measurement cell with an inner diameter of 11 mm that could isolate it from external air, and a pressure of 5 MPa was applied by bolts. Subsequently, the measurement cell was sealed. In addition, the process from the fabrication of the sulfide-based solid electrolyte particles to the sealing of the evaluation cells was carried out in a glove box under an Ar atmosphere. Evaluation cells for each test number were fabricated according to the above process.

[0181] Cyclic voltammetry (CV) tests were performed using the manufactured evaluation cells with various test numbers. In the CV test, the test cell was used as the working electrode, and metallic Li foil was used as both the counter and reference electrode. Specifically, for the evaluation cells maintained at 60°C for 24 hours, the voltage was measured from the open-circuit voltage V... OC (V) After scanning to 3.0V, it scans to 0.005V, and then scans to the open circuit voltage V. OC (V), measuring the current density of the flow (μA / cm). 2 The scan rate is set to 5 mV / second. Additionally, the open-circuit voltage V... OC The voltage was 2.0–2.5V in the evaluation cells for any of the test numbers.

[0182] Based on the measurement results, the open-circuit voltage V was measured within the time (seconds) consumed by the scan. OC Current density (μA / cm²) flowing during the scan from (V) to 3.0V 2 The cumulative value is calculated. Furthermore, to eliminate the influence of minor unevenness on the evaluation surface of the test piece, this cumulative value is divided by the unfolded area ratio Sdr. The resulting value is defined as the cumulative current value C (μC / cm²). 2 Let be the index representing the degree of corrosion reaction in the test piece. That is, the cumulative current value C (μC / cm). 2 ), when the open circuit voltage V OC The time elapsed from the start of the scan from (V) to 3.0V is defined as the test time t (seconds), the time to reach 3.0V is defined as t3.0 (seconds), and the current density flowing in the battery at the test time t (seconds) is defined as I(t) (μA / cm). 2 When the unfolded area ratio of the test piece is set as Sdr, it is obtained by the following formula.

[0183] [Formula 1]

[0184]

[0185] The obtained cumulative current value is 1000 μC / cm. 2 The following conditions are considered to indicate that the test number exhibits excellent corrosion resistance (E (Excellent) in the corrosion resistance column of Table 4). On the other hand, the obtained cumulative current value exceeds 1000 μC / cm. 2 In this case, the test number is evaluated as not having excellent corrosion resistance (in Table 4, the corrosion resistance column shows "NA (Not Acceptable)").

[0186] [Evaluation Results]

[0187] Referring to Table 4, the number density of specific particles in the stainless steel foils of tests 2 and 4, within the stainless steel foil matrix, was 40.0 particles / cm². 2 In these cases, the ratio of specific particles to coarse particles is over 80%. As a result, these stainless steel foils reduce damage formation and exhibit excellent corrosion resistance.

[0188] On the other hand, in test number 8, the stainless steel foil had a specific particle density exceeding 40.0 particles / cm² within the stainless steel foil substrate. 2 The proportion of specific particles relative to coarse particles is less than 80%. As a result, the stainless steel foil does not reduce damage formation and does not exhibit excellent corrosion resistance.

[0189] In test 10, the stainless steel foil had a specific particle size distribution relative to coarse particles of less than 80% within its stainless steel foil body. As a result, this stainless steel foil did not reduce damage formation and did not exhibit excellent corrosion resistance.

[0190] The embodiments of this disclosure have been described above. However, the above embodiments are merely illustrative for implementing this disclosure. Therefore, this disclosure is not limited to the above embodiments, and the above embodiments can be appropriately modified and implemented without departing from its spirit.

Claims

1. A stainless steel foil, It has a foil body made of stainless steel. In any facet of the foil body, Particles with an equivalent circumference diameter of 6.0 μm or more are defined as coarse particles. Among the coarse particles Among the elements contained in the particles, Al, Mg, or Ti have the highest content. When particles whose Al content, Mg content, and Ti content satisfy equation (1) are defined as specific particles, The number density of the specific particles is 40.0 particles / cm³. 2 the following, The specific particles constitute more than 80% of the total number of coarse particles. 0.3591≦4.5579Al / (Al+Mg+Ti)-4.5579Mg / (Al+Mg+Ti)+1.7321Ti / (Al+Mg+Ti)≦3.0943 (1) in, In the element symbols of formula (1), the Al, Mg and Ti contents contained in the coarse particles are substituted by mass%; if the coarse particles do not contain the corresponding elements, "0" is substituted into the element symbols.

2. The stainless steel foil according to claim 1, In the foil body, Among the specific particles When defining a specific spinel particle as one whose Ti content satisfies equation (2) among the elemental contents of the particles, The number density of the specific spinel grains is 4.5 grains / cm³. 2 the following, Ti / (Al+Mg+Ti)≦0.05 (2) in, In the element symbols of formula (2), the Al, Mg and Ti contents contained in the coarse particles are substituted by mass%; if the coarse particles do not contain the corresponding elements, "0" is substituted into the element symbols.

3. The stainless steel foil according to claim 1, The chemical composition of the foil body, in mass % is Contains Ti: 0.10–1.00%.

4. The stainless steel foil according to claim 2, The chemical composition of the foil body, in mass % is Contains Ti: 0.10–1.00%.

5. The stainless steel foil according to any one of claims 1 to 4, The foil body is made of ferritic stainless steel or austenitic stainless steel.

Citation Information

Patent Citations

  • Ferrite-based stainless foil for solar battery substrate use

    JP2014183254A

  • Ferritic stainless steel foil and production method for same

    WO2016031192A1

  • Stainless foil current collector for secondary battery positive electrodes

    WO2020004595A1